Analisis strategi Pusat Investasi Pemerintah dalam menghadapi holding ultra mikro dengan pendekatan porter’s five forces - Oktavianus Oki Bagus Krisnawan (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
As an entity engaged in the distribution of ultra-micro financing, Badan Layanan Umum Pusat Investasi Pemerintah (BLU PIP) has several competitors. This has an impact on conditions of high competition among these ultra microfinance providers. The competitors as referred to can be in the form of Public Service Agencies, Banks, Non-Bank Financial Institutions, or Peer-to-Peer Lending Fintech Platforms. In addition to being faced with these competitive conditions, BLU PIP is also faced with a new threat, namely the implementation of ultra micro holding carried out by PT Bank Rakyat Indonesia Tbk together with PT Pegadaian and PT Permodalan Nasional Madani. This study aims to determine the strategy analysis and strategy implementation of BLU PIP in dealing with ultra micro holdings. The analytical technique used in this research is descriptive qualitative with the Porter’s Five Forces approach. The data were obtained from document reviews and in-depth interviews. From the results of research using Porter's five analyses, it is concluded that BLU PIP has a fairly high level of value on the assessment of competitive conditions in similar industries, the threat of new entrants, the bargaining power of suppliers, and the bargaining power of buyers. Meanwhile, there is no threat to substitute products. This study recommends several things to BLU PIP, namely to focus more on initiating cooperation with new cooperatives using a direct distribution scheme, differentiating aspects of assistance to debtors, and distributing financing through direct lending mechanisms.